(untitled) (lectio difficilior, 2005)
There is scarcely any dispute that women participated in early Christian meal gatherings. But scholars agree that although this praxis of Christians would not have been unique, it would have been noticed. This article examines the representation of women in the Greco-Roman symposium. I argue that Greco-Roman literature on the symposium is not as much a reflection of women’s actual meal praxis as it uses women figuratively to make a point about something else. These texts introduce the subject of ‘women at the symposium’ primarily as a rhetorical strategy of describing what constitutes an ideal or corrupt symposium and meal praxis. But there is an important gap in this literature. The texts do not address those symposia where women in antiquity are predominantly present, namely religious symposia and meals related to family events (weddings and funeral banquets). Thus, the attention to women leads away from the culture of the symposium among friends, philosophers, and clients portrayed prevalently in the symposium literature and towards contexts in which meals are part of religious and familial gatherings. In those contexts women’s participation in meals would not have been noticed. It is further argued that different symposium cultures are at issue in the Gospels of Mark and Luke. Therefore these Gospels depict women’s participation in meals differently. The role of women in meals related to family events and funeral rites leads to the hypothesis that women took a central role at the origin of the Lord’s Supper.